2016
DOI: 10.1080/15459624.2016.1167278
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the Nanoparticle Emission Assessment Technique into the Nanomaterial Exposure Assessment Technique (NEAT 2.0)

Abstract: Engineered nanomaterial emission and exposure characterization studies have been completed at more than 60 different facilities by the National Institute for Occupational Safety and Health (NIOSH). These experiences have provided NIOSH the opportunity to refine an earlier published technique, the Nanoparticle Emission Assessment Technique (NEAT 1.0), into a more comprehensive technique for assessing worker and workplace exposures to engineered nanomaterials. This change is reflected in the new name Nanomateria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…The Field Studies Team observed work practices used during the production or use of ENMs and the use of PPE, including respiratory protection (if any), during each of the 11 evaluations 1,16) . It is also important to consider the non-nanomaterial chemicals that may be used to prepare or process ENM-containing slurries 1) .…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Field Studies Team observed work practices used during the production or use of ENMs and the use of PPE, including respiratory protection (if any), during each of the 11 evaluations 1,16) . It is also important to consider the non-nanomaterial chemicals that may be used to prepare or process ENM-containing slurries 1) .…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
“…This document also grouped sampling results from several NTRC on-site studies. With increased understanding of nanomaterial uses, controls, and sampling techniques, NIOSH issued NEAT 2.0 1) , an updated version that is currently used as a framework for NIOSH/NTRC Field Studies Team evaluations. The original NEAT made use of direct reading instruments (DRIs) to identify workplace tasks associated with nanoparticle emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers had assessed the problem of selecting the suitable method for the preparation of nano particles [32]. Nano sensors contribute to the specificity, sensitivity, and performance of the methods and improved by using nano materials for their construction [23,33]. The nanotechnology based biosensor or nano biosensor technology is revolutionizing the health care industry such as the nano biosensor technology which is used in the measurement of metabolites, monitoring of diabetes forensic medicine, homeland security [34].…”
Section: Analytical Techniques Employed In Nanotechnologymentioning
confidence: 99%
“…16 The best available guidance for exposure measurement suggests that in addition to an appropriate characterisation of particle size distribution, measurements should at least encompass an assessment of mass, but where possible also include number and/or surface area concentration. 17,18 Confronted with these limitations, it was decided that the most sensible course of action is to focus on (i) qualitative risk assessment covering all 1 In addition, input from (i) experts in the NanoSafety Cluster (NSC) community, (ii) EU institutions (e.g., ECHA), (iii) international organisations (e.g., OECD 27 ), (iv) industry initiatives (e.g., ECETOC 28,29 ), (v) European Center for Nanotoxicology (EURO-NanoTox), 54 and (vi) peerreviewed scientific literature, have been considered to ensure consistency at EU level and alignment to the stateof-the-art.…”
Section: Introductionmentioning
confidence: 99%